The Most Appropriate MARC Format for Farsi Printed Books and Digital Resources. Issue 2 (3rd April 2017) - Pashootanizadeh, Mitra; Kokabi, Mortaza
ABSTRACT: The purpose of this research is to determine the appropriate MARC format for Farsi printed books and digital resources considering the present situation of MARC and information organization in Iran. For this purpose, a descriptive research methodology was applied and a researcher-made questionnaire survey instrument was designed to investigate the viewpoints of Iranian MARC experts concerning MARC use in Iran. A 5-point Likert-type scale checklist was for collecting the experts' perceptions about the importance of each MARC criterion. Iranian MARC experts were asked to express their viewpoints. The respondents were identified using the "snowball" sampling method. Findings revealed that by making some modifications to UNIMARC, we could meet the cataloguing requirements of the most widely used information resource in Iran, the printed book; however, due to the rapid growth of digital resources, the tendency to use them in Iran, and the limited capabilities of UNIMARC (i.e., having no link to digital resources and having no metadata schemes such as MARCXML, MODS, METS, and MADS), UNIMARC does not seem to guarantee a better future for development of library systems compared with MARC21.